Best Answer

"a" plus "3a" is equal to 4a. (3a+a=4a). You already have 3 "a's" and then you add another "a."

Q: What is the answer of this problem-a plus 3a?

Write your answer...

Submit

Still have questions?

Continue Learning about Algebra

What is the solution of -2a plus 3a plus 5b

It can be simplified to: 3a^2 +10a+7 or factored as (3a+7)(a+1)

The given expression can be simplified to: 3b-a

3a + 2a = 5a

a + 3a + 5a = 180 9a =180 a = 20

Related questions

7a minus 2, if "3a-2" means 3a minus 2. 3a plus 1 and 1-3rd in parenthesis times 3a, if "3a-2" means 3a squared. a plus 3a squared plus 3a = 1-3rd times 3a plus 3a times 3a plus 1 times 3a = 3a plus 1 and 1-3rd in parenthesis times 3a

It is 6a + 4

What is the solution of -2a plus 3a plus 5b

a + 3a - 2 + 3a. Add the a + 3a + 3a = 7a. You can't combine the -2 & 7a so the solution is: 7a - 2.

3a+5b+7a=

6a-3

3a squared plus nine = 19a. 3a to the second power = 9a plus 9 = 19a.

-7a + 3a = -4a

2a + 5a + 3a = 10a

-2(3a+2)+2=

3a + (3b - 2a) + 5b =3a + 3b - 2a + 5b =(3a - 2a) + (3b + 5b) =a + 8b

If a + b = 6, what is the value of 3a + 3b?